2021
DOI: 10.1021/acsfoodscitech.0c00148
|View full text |Cite
|
Sign up to set email alerts
|

Rest Plant Materials with Natural Antioxidants Increase the Oxidative Stability of Omega-3-Rich Norwegian Cold Pressed Camelina sativa Oil

Abstract: Quality of Norwegian cold pressed camelina oil for human consumption and fish feed production, with special focus on plant rest materials, natural antioxidants and oxidation products are studied. Both crude oil with plant rest materials (CCO), and centrifuged oil (CO) were highly unsaturated with 39.4 % (w/w) α-linolenic acid. The oils were oxidatively stable for 12 months at long-time storage conditions at 4°C. Lipid oxidation was observed in CO, but not in CCO, between 6 and at 9 months at 20 °C. This differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…Tomato by-products inhibited the DPPH radical and the iron reducing power (FRAP). This high antioxidant capacity may be due to their content of antioxidant compounds such as phenolics, carotenoids and vitamin C [ 22 ]. Therefore, these by-products may prevent the body from oxidative stress and cardiovascular and cancerous diseases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomato by-products inhibited the DPPH radical and the iron reducing power (FRAP). This high antioxidant capacity may be due to their content of antioxidant compounds such as phenolics, carotenoids and vitamin C [ 22 ]. Therefore, these by-products may prevent the body from oxidative stress and cardiovascular and cancerous diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Foods rich in omega-3 fatty acids protect against the risks of occurrence of cardiovascular diseases and mortality [ 21 ]. Unfortunately the stability of omega-3, due to poly-unsaturation, is a major problem for conservation and requires the presence of antioxidants [ 22 ]. Of all the benefits of tomato seed oils, its consumption may be encouraged because of its composition in bioactive compounds that have proven to have positive effects on human health [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…All the studies confirmed that these two ω3 LC-PUFA canola events (NS-B5ØØ27-4 and LBFLFK) were as substantially equivalent as conventional canola varieties; the only difference observed was the expected oil profile change [37,62]. Fish feeding trials also demonstrated that DHA canola oil [62][63][64] or Camelina EPA oil [65][66][67][68] were safe and effective alternatives to fish oil in the fish diet. Another study using ω3 LC-PUFA canola oil to replace menhaden fish oil in shrimp diets also showed no significant differences in shrimp performance metrics [69].…”
Section: The Challenge Of Deregulationmentioning
confidence: 64%
“…Linoleic acid (18:2 n-6) and α-linolenic acids (18:3n-3) were the main PUFAs with 16% (w/w) and 37% (w/w), respectively. Oil samples with different oxidation degrees for the in vitro cell trial were produced by incubation of oil samples in the dark at 40 0 C with access to oxygen for 2, 4, 6, and 9 weeks as described in Nilsson et al [21]. Initial samples (CO-0w) and samples taken after 2 w, 4 w, 6 w, and 9 w (CO-2w, CO-4w, CO-6w, CO-9w) were flushed with nitrogen and frozen at -80 • C immediately after sampling.…”
Section: Dietary Oil With Different Degrees Of Oxidationmentioning
confidence: 99%
“…The content of the omega-6 fatty acid LA in camelina oil is about half of the ALA content. We have recently shown that plant rest materials with natural antioxidants can increase the oxidative stability of an omega-3 rich Norwegian cold-pressed Camelina sativa oil [21]; however, increased oxidation and elevated levels of 4-hydroxy-2-alkenals were observed during storage experiments.…”
Section: Introductionmentioning
confidence: 99%